The impact of the personality development programme for conflicts victims at Pesantren Yatim Assyafi'Iyah Jakarta Indonesia - Sidrotul Muntaha (Institute of Education, International Islamic University Malaysia, 2010)
This study examined the impact of the personality development programme on conflict victims at Pesantren Yatim Assyafi'iyah Jakarta,Indonesia and to investigate the impact of the school's programme meant to develop the students' personality development which includes the nature the programme, such as important subjects for them, the spiritual activities, the practical! skills, the entrepreneurship programme, the sports programme, the community service and the art programme for them. This study also examines the factors affecting the participants' personality during the post conflict period such as the environmental factor, the family factor, the conflict effect factor, teacher and caregiver factor and peer factor. To achieve these purposes two major methods of data collection are used; library research and field study. The latter involves interviews with students the school and direct observation. In addition, questionnaires are distributed to three respondents in order to validate and justify the data obtained through observation and interviews. The findings of the study showed that this particular school has facilities and programme for their students to enhance their personality. The programme aims to enhance mind, skills and develop the feeling of how to be trusted among students. The findings also indicated that the programme in this school emphasis on producing students who can apply knowledge in real life and preaching it to others. However, the teachers' and students' perception of the problems faced by Pesantren Yatim Assyafi'iyah, Jakarta refer to various problems such as financial problem and lack of government support. Most teachers in this school agreed that the financial problem is the main problem faced at Assyafi'iyah. Many problems are further compounded by other problems such as teacher qualification, administration and management problems, student discipline and achievement. Hence, this school is always trying to secure source of funds in order to slowly solve many arising issues.